Education: a process of humanization (Research, Society and Development, 2018)
The present study takes as object of study the contribution of the Educational Advisor in the interpersonal relations between the faculty, students and families. In order to analyze the importance of the presence of the Educational Advisor in the schools of the SEB group - Brazilian Educational System in Bahia, whose project was submitted and approved by the Research Ethics Committee of UFBA (Federal University of Bahia). The research was carried out in four schools in Bahia, three in the municipality of Salvador and one in the municipality of Lauro de Freitas. We opted for the exploratory qualitative approach. Thus, a semi-structured interview was conducted as research devices. From the basic question about what the faculty, student and family think about the work of the Educational Advisor? For that, the contributions of Grinspun (1994/2010) were searched as theoretical framework; CONCEIÇÃO, (2010); Giacáglia and Penteado (2010); Morin (2010), with current information and of extreme relevance to the studied subject, providing the enrichment of the research with scientific foundation. The results pointed out that the work of the Educational Guidance in the context of the different units of the private school investigated, was characterized by a pedagogical dimension much more comprehensive, having its functions demarcated and valued. This professional has a mediating role with the other educators, acting together with all the actors of the school to facilitate interpersonal relationships, in the rescue of a more effective and reflexive action, aiming to qualify education in the school units, making them conscious individuals, reflective and respectful of differences and collectivity.